Thrombotic microangiopathy with irreversible renal function in a CKD patient following COVID-19: case report - Qin, Yunlong; Yang, Xinjun; Zhao, Wei; Li, Yuzhe; Bai, Yaling; Wang, Lihui (Frontiers in Medicine, 2025)
We report a case of chronic kidney disease (CKD), in a patient with normal renal function, diagnosed as acute renal failure stage 3 after coronavirus disease 2019 (COVID-19)-associated thrombotic microangiopathy (TMA) characterized by the presence of thrombocytopenia, microangiopathic hemolytic anemia, and acute renal failure. The results of the renal biopsy were thickening of the small artery wall with mucous edema, endothelial swelling and hyperplasia, and segmental endothelial onion-like hyperplasia. However, the pathogenesis factors of the patient who suffered from COVID-19-associated TMA were not clear, although blood complements, activity of ADAMTS13, and Factor H were detected as normal. After the administration of pulse glucocorticoid, plasma exchange, and hemodialysis, the patient developed chronic renal failure and depended on peritoneal dialysis 12 months later. Although the clinical manifestations of TMA are similar, the etiology and pathogenesis are very complex. It is very important to determine the pathogenesis of TMA to proceed with precise treatment to improve the prognosis of the patient.